PERAN MAHASISWA DALAM MENINGKATKAN KESADARAN MASYARAKAT UNTUK MEMUTUS MATA RANTAI PENYEBARAN COVID- 19 DI KELURAHAN NEROKTOG - Denny, Yus Rama; Afrilia, Rilva; Halimatusa’diyah, Syifa; Wati, Peradea; Hafith, Muhammad; Yulianti, Ria Retno; Azzahra, Zalza Afni (Jurnal Pengabdian Dinamika, 2021)
This articlerelates totheroleofstudents inincreasingpublicawareness oftheNeroktogUrbanVillage, TangerangCityaspartoftheStudentWorkLectureActivities(KKM).This activityaims tosocializeandprovide informationaboutthe importanceofimplementingstricthealthprotocolsasaformofeffortindecidingand minimizingthespreadofthecoronavirus.Themethodusedinconductingthissocializationisthroughcounseling andprovidinginformationinthe form ofpostersaboutthe importance ofwearingdouble masks,implementing healthylivingbehaviors,thebenefitsof following vaccines,andhealthprotocolsusedwhenleavingthehouse. Thisactivitywascarriedoutonlinebyproviding thisinformationthroughpostson Instagramand WhatsApp groupsofNeroktogVillageresidents.Theresultsofthis socializationactivityareexpectedafterthe implementationoftheThematicKKM, itisimportantthatparticipants andresidents ofNeroktogVillagealready knowabouttheimportanceofimplementinghealthprotocols.However,inpracticeitturnsoutthattheawareness ofthesurroundingcommunityregardingtheimportanceofimplementinghealthprotocols is stilllacking, especiallyregardingmaintainingasafe distance.Inaddition,people'smobilityoutsidethe houseisstilldifficult tocontrol,eitherfor workorjustgoingoutofthehouse.Withthis socialization,itishopedthattheparticipants withtheirauthorityas villageofficialscantransmittheirknowledgeandunderstandingtothecommunity, especiallytheresidents ofNeroktogVillage